Revisiting metal electrodeposition in porous anodic alumina: toward tailored preparation of metal nanotube arrays - Zhang, Aiqin (2018)
Metal electrodeposition in porous anodic aluminum oxide (AAO) is a complicated and multi-step process, consisting of diffusion of metal ions in the pores, reduction of metal ions and crystallization of metal atoms. The growth mechanism is also complex and changing with electrodeposition conditions. In this paper, we present new insights into the growth of metal nanostructures in AAO via electrodeposition. Two different growth modes for metal electrodeposition in porous AAO, namely center growth mode and lateral growth mode, are revealed, opening a new approach to preparing metal nanotube arrays with tailored structures. This strategy is broadly applicable to varieties of metals, such as Ni, Cu, and Ag. The resultant metal nanotube arrays give rise to improved electro-catalytic activity to small molecule oxidation (such as ethanol and urea) due to the larger surface areas. These findings help to deeply understand the metal electrodeposition in AAO, extend the application of template-assisted electrodeposition and provide innovative ideas to prepare novel metal nanomaterials.